2018
DOI: 10.1016/j.avsg.2018.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Directed Thrombolysis Versus Pharmacomechanical Thrombectomy for Upper Extremity Deep Venous Thrombosis: A Cost-Effectiveness Analysis

Abstract: The clinical results of the treatment of UEDVT with CDT or PMT were similar. However, PMT required shorter hospital stay and less intensive surveillance, leading to lower total costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Our results are comparable with previous publications, although the patients in these studies all had acute DVT. 22 In addition, the clinical efficacies of lysis for the PMT group were 86.67% (26/30) and for the CDT group was 65.91% (29/44) in our study. Our results are not quite comparable to those reported by Lin et al 23 Compared with the PEARL data, the clinical efficacy of lysis of PCDT is higher than the efficacies reported in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Our results are comparable with previous publications, although the patients in these studies all had acute DVT. 22 In addition, the clinical efficacies of lysis for the PMT group were 86.67% (26/30) and for the CDT group was 65.91% (29/44) in our study. Our results are not quite comparable to those reported by Lin et al 23 Compared with the PEARL data, the clinical efficacy of lysis of PCDT is higher than the efficacies reported in our study.…”
Section: Discussionsupporting
confidence: 52%
“…While PMT devices have been shown to decrease overall treatment time, exposure to tPA, and length of stay compared to traditional CDT or systemic thrombolytics, they also cause significant red blood cell hemolysis due to high pressure spray mechanics. 12,13,16 The PEARL AngioJet registry reported 5% of enrolled patients required dialysis related to the use of the device, though the overall incidence of AKI was not described. 17 In 2017, Escobar et al reported that 29% of patients treated with AngioJet developed AKI compared to 8% of patients managed with CDT.…”
Section: Discussionmentioning
confidence: 99%
“…11 Complications using PMT methods include major bleeding and hemolysis, which may limit their utility in certain instances, particularly in those patients with cardiac arrhythmias and hyperkalemia. 12,13 The Penumbra Indigo aspiration thrombectomy system is a device for venous and arterial thrombectomy within the peripheral and coronary vasculature. It is a one-time use device designed for aspiration of fresh arterial or venous thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…PCDT required shorter hospital stay and less intensive surveillance leading to lower total cost. 298 In a nonrandomised retrospective analysis of 103 patients who had 110 first rib resections, 45 subclavian veins underwent thrombolysis with or without venoplasty prior to first rib resection and were compared with 65 subclavian veins treated by pre-operative anticoagulation alone. Around 91% of veins were patent in asymptomatic patients at the 16 month follow up in each of the two groups.…”
Section: Treatmentmentioning
confidence: 99%